THE BUSINESS ANALYSIS PROCESSING OF CRAB (Portunus pelagicus) AT SUNGAI BULUH VILLAGE, SINGKEP BARAT SUB DISBRICT, LINGGA REGENCY RIAU ISLAND PROVINCE - Arifin Khairul Hakim; Hendrik '; Ridar Hendri (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research about business analysis of crab (Portunus pelagicus) processing was conducted on May 2015 at Sungai Buluh Village, Singkep Barat, Lingga Regency, Riau Island Province. This research aimed to analyzed production development, profit investation, business fersibility, and job prospect processing of crab. The method used in this researh was study case method and respondent determination with purposive sampling is business owner, labor, fisherman, and traders. The result of this research showed production had affected by season and business investation processing of crab is 83.507.000 with criteria invest of processing is ACR 1.13, FRR 460.8 % and PPC 0.22 %, it showed business processing of crab is feasible to continued based on criteria invest and have good prospect based on marketing and environment.Keywords : Crab, Portunus pelagicus , Business fersibility, Investation